Strategi Pengembangan Usaha Ikan Nila Salina (Oreochromis sp.) Sebagai Varietas Baru Budidaya Perikanan - Dewi, Kiki Mariya; Hubeis, Aida Vitayala S; Raharja, Sapta (Institut Pertanian Bogor, 2018)
Salina is a high salinity tolerant hybrid tilapia seed of genetic improvement that can grow well in brackish water that has salinity more than 20ppt or even in marine water with salinity up to 32ppt through the utilization of character euryhaline tilapia. Salina has been oficially by the Ministry of Marine Affairs and Fisheries in March 2014 based on the Decree of the Minister of Marine Affairs and Fisheries of the Republic of Indonesia Number 22/KEPMEN-KP/2014 on the Release of Salina Tilapia with commercial name Salina (Saline Tolerance Indonesian Tilapia). This study aimed to identify the financial feasibility as well as internal and external Salina culture factors in order to formulate the development strategy of Salina tilapia culture. The method used was quantitative descriptive analysiswhich consists of a matrix Internal Factor Evaluation (IFE), External Factor Evaluation (EFE),Internal-External (IE), Strength-Weakness-Opportunities-Threats(SWOT), andAnalytic Hierarchy Process (AHP) as a decision-making methods. The instruments used in the financial analysis were BEP, NPV, IRR, Net B/C Ratio, and PP. Based on financial analysis, Salina culture was feasible. While the result of the calculation of IFE is 2.18 and EFE is 3.10, positioning the Salina cell II. The results of the AHP assessment stated that the strategic priority of the strategy was to conduct promotional and socialization activities to introduce Salina as well as to attract public interest and increase demand.